2019
DOI: 10.1007/s10803-019-03975-5
|View full text |Cite
|
Sign up to set email alerts
|

Social Decision Making in Autistic Adolescents: The Role of Theory of Mind, Executive Functioning and Emotion Regulation

Abstract: Title Social decision making in autistic adolescents: the role of theory of mind, executive functioning and emotion regulation Running head

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
31
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(38 citation statements)
references
References 85 publications
(83 reference statements)
3
31
0
3
Order By: Relevance
“…In previous studies, fairnessrelated behaviours were shown to be related to ToM development defects (45), but no consistent conclusion was found in our study. At the same time, we found that the unfair acceptance rates of children and adolescents with HF-ASD are related to BRIEF scores, which is consistent with previous results (10,11,13,14). Further regression analysis shows that both GEM and working memory have an impact on the unfair acceptance rate of individuals with TD, while the interaction between the BRIEF scores of individuals with HF-ASD and age can negatively predict unfair acceptance rates.…”
Section: The Association Between Unfair Acceptance and Tom And Ef In supporting
confidence: 91%
“…In previous studies, fairnessrelated behaviours were shown to be related to ToM development defects (45), but no consistent conclusion was found in our study. At the same time, we found that the unfair acceptance rates of children and adolescents with HF-ASD are related to BRIEF scores, which is consistent with previous results (10,11,13,14). Further regression analysis shows that both GEM and working memory have an impact on the unfair acceptance rate of individuals with TD, while the interaction between the BRIEF scores of individuals with HF-ASD and age can negatively predict unfair acceptance rates.…”
Section: The Association Between Unfair Acceptance and Tom And Ef In supporting
confidence: 91%
“…In previous studies, fairnessrelated behaviours were shown to be related to ToM development defects (46), but no consistent conclusion was found in our study. At the same time, we found that the unfair acceptance rates of children and adolescents with HF-ASD are related to BRIEF scores, which is consistent with previous results (11,12,14,15). Further regression analysis shows that both GEM and working memory have an impact on the unfair acceptance rate of individuals with TD, while the interaction between the BRIEF scores of individuals with HF-ASD and age can negatively predict unfair acceptance rates.…”
Section: The Association Between Unfair Acceptance and Tom And Ef In supporting
confidence: 91%
“…If not, both parties receive an amount of 0. The results showed that there was no significant difference between those with HF-ASD and those with typical development (TD) when in the role of recipient (11). Other researchers indicated that children with HF-ASD whose age between 6~16 years old were more likely to accept unfair distribution, and they claimed that this higher acceptance rate might be related to defects in theory of mind (ToM), which is the ability to understand and predict others' feelings and behaviours (12,13).…”
mentioning
confidence: 97%
See 2 more Smart Citations